Schaftoside contributed to anti-inflammatory activity of Clinacanthus nutans extract in lipopolysaccharide-induced RAW 264.7 cells - Thongyim, Saruda; Sattayawat, Pachara; Pongamornkul, Wittaya; Jangsutthivorawat, Siriphorn; Tragoolpua, Yingmanee; Panya, Aussara (Frontiers in Pharmacology, 2025)
IntroductionClinacanthus nutans: a plant listed in the Thai Herbal Pharmacopoeia, is well recognized for its medicinal properties, particularly its anti-inflammatory and antiviral activities. Among its known bioactive constituents, schaftoside has been reported to exhibit anti-inflammatory effects in various disease models. However, comparative studies between pure schaftoside and C. nutans crude extracts, as well as comprehensive investigations into the underlying mechanisms of action, remain limited. Moreover, the relationship between the quantity and diversity of bioactive compounds and their corresponding anti-inflammatory activity which could serve as potential quality biomarkers has not been fully elucidated.MethodsIn this study, we investigated the anti-inflammatory effects of schaftoside and evaluated its content in C. nutans ethanolic extracts collected from ten geographically distinct regions of Thailand. First, the anti-inflammatory activity of schaftoside was assessed in LPS-induced RAW 264.7 macrophage cells. Subsequently, ten C. nutans ethanolic extracts were tested for their anti-inflammatory activity in the same cell model. To further explore the potential contribution of schaftoside and other bioactive compounds to anti-inflammatory activity, molecular docking analysis was performed.Results and DiscussionAt a concentration of 40 μM, schaftoside significantly downregulated the expression of key inflammation-related genes, including iNOS, COX2, PGE2, PGE4, TNF-α, and IL6. All extracts demonstrated a consistent trend of reducing iNOS protein expression, which was accompanied by a corresponding decrease in nitric oxide (NO) production, indicating their potential anti-inflammatory properties. However, no significant correlation was observed between schaftoside content and the magnitude of anti-inflammatory activity, suggesting that schaftoside may not be the sole active compound responsible for the observed effects. The results of molecular docking analysis revealed that, in addition to schaftoside, other flavonoids such as isoorientin and isovitexin also exhibited binding affinity toward the iNOS protein, indicating that these compounds may contribute to the overall anti-inflammatory activity of C. nutans extracts.